Acceptability of a parent-focused program for physical literacy development among parents and children during the COVID-19 pandemic: A qualitative study - Ha, Amy S.; Zeng, Taoran; He, Qing; Chan, Cecilia H. S.; Fung, Ying; Ng, Johan Y. Y. (Frontiers in Public Health, 2022)
Background A 3-month parent education program was designed and implemented in Hong Kong to improve physical literacy (PL) among primary school children and their parents during the COVID-19 pandemic. This study aims to probe into the acceptability of the intervention from parental perspectives, providing more insights for future implementation. Methods Following the 3-month parent-focused PL program, 16 parents (mean age = 43.73 years, 15 mothers) were recruited to participate in semi-structured individual interviews in June 2021. Interviews were analyzed using thematic analysis in NVivo 12. Two coders analyzed interview transcripts deductively based on the interview guide and social cognitive theory (SCT). Results Three themes were identified that captured the acceptability of the program: (1) Addressing needs through appropriate delivery enhances acceptability of intervention; (2) Positive behavioral and psychological changes to families; (3) Appropriate support of environmental factors can enhance the sustainability of program effects. The high levels of acceptability were attributable to the fact that parents were able to learn and be a gatekeeper to impact their children positively. Moreover, the design and contents of the program were appropriate for the participating parents because the program provided adequate learning resources and interactive learning support without being overly rigid, and the online learning mode was feasible and convenient. Consequent to their participation in the program, parents expressed that they became more aware of the importance of PL, established physical activity routines with their children, and modified their parenting styles which resulted in improved parent-child relationships. Conclusions The current study provided evidence that engaging parents in the intervention was feasible and acceptable approach in supporting both parents and children to establish physically active routines in the family setting. The insights gained regarding the appropriateness and acceptability of the program in this specific context may be used to inform the design, implementation and sustainability of other parent-focused PL programs.